Morphometric features and performance of Nagfani goats in their native tract - Bhateshwar, Vinod; Bhinchhar, Basant Kumar; Kharkwal, Sheela (Journal of Livestock Biodiversity, 2025)
Nagfani goat is the most adaptable, dual purpose (chevon and milk), widely distributed and prominent goat in Alwar, Bharatpur and nearby districts of Rajasthan state in India. In order to study the morphometric features and performance of Nagfani goat, the first field survey in India was conducted at their native tract in Alwar and Bharatpur districts of Rajasthan in the year 2023-24. According to the interview schedule, a total of 29 villages were randomly selected based on the Nagfani goat population and 185 goat keepers were randomly selected for this study. Measurements of the data related to morphometric features and performance were taken at different age groups of 9650 animals. The size of Nagfani animals typically ranges from medium to large. The white colour coat with black or pale red spots on the body was a significant characteristic of the Nagfani goat. Ears length was 29.28±0.25 cm, the lower part of the ear hanging about 2 to 3 cm away from its face and remaining fully open in the front like a Nag/Cobra hood, making it stand out from other goats. The nose line exhibited Roman shape characteristic. Horns are of medium length with 17.05±0.99 cm, twisted and directed backward horns. Dewlap was well developed in male goats. The tail was observed in the medium length of 20.65±0.27 cm. The overall body weight of male and female individuals from birth to adulthood were recorded as 3.65±0.02 to 89.51±0.73 kg and 3.60±0.02 to 64.42±0.18 kg, respectively. The average overall chest girth, body length and height at withers was recorded as 54.86±0.63, 51.59±0.61 and 53.35±0.63 cm in male goats and 77.76±0.22, 75.45±0.21 and 75.72±0.22 cm in female goats respectively. The milk yield was recorded at 983.71±1.85 gm/day with richer milk constituents of 3.27±1.01% fat and 8.14±0.02% SNF respectively. The average lactation length in lactating goats was recorded as 281.42±0.30 days. The first mating age was 414.07±3.60 days in males and 310.39±1.57 days in females. Female goats had their first oestrus at 310.23±1.58 days, with a cycle duration of 20.52±0.19 days respectively. The first kidding occurred at 514.88±1.66 days, with an average kidding interval of 368.36±0.64 days. In Nagfani goats, the average litter size was 1.99±0.01 and the lifetime number of kiddings was recorded as 10.94±0.85.